2014
DOI: 10.1016/j.drugalcdep.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Frequent binge drinking five to six years after exposure to 9/11: Findings from the World Trade Center Health Registry

Abstract: Background Exposure to 9/11 may have considerable long-term impact on health behaviors, including increased alcohol consumption. We examined the association between frequent binge drinking, posttraumatic stress disorder (PTSD), and number of 9/11-specific experiences among World Trade Center Health Registry (Registry) enrollees five-to-six years after 9/11. Methods Participants included 41,284 lower Manhattan residents, workers, passers-by, and rescue/recovery workers aged 18 or older without a pre-9/11 PTSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Consistent with our EMS findings, previous 9/11 health studies found increased risks among WTC-exposed cohorts for aerodigestive conditions such as GERD6 and asthma,5 as well as for symptoms indicative of PTSD,7 depression,8 and harmful alcohol use 9. Unlike prior studies, ours is the first to concentrate on EMS workers, especially important as we used confirmed physician diagnoses from FDNY medical records rather than self-reports to describe the post-9/11 cumulative incidence of physical health conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our EMS findings, previous 9/11 health studies found increased risks among WTC-exposed cohorts for aerodigestive conditions such as GERD6 and asthma,5 as well as for symptoms indicative of PTSD,7 depression,8 and harmful alcohol use 9. Unlike prior studies, ours is the first to concentrate on EMS workers, especially important as we used confirmed physician diagnoses from FDNY medical records rather than self-reports to describe the post-9/11 cumulative incidence of physical health conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Rescue and recovery workers included first responders—firefighters, police officers and emergency medical service (EMS) workers—as well as operating engineers, iron workers, railway tunnel workers, sanitation workers, utility workers, and volunteers 1. Previous research has documented an array of WTC-related physical and mental health issues among these workers including: excess cancer risks;2–4 elevated rates of aerodigestive illnesses such as asthma5 or gastroesophageal reflux disease (GERD);6 and, increased risks of post-traumatic stress disorder (PTSD),7 depression,8 and frequent binge drinking 9. Substantial comorbidities between these health conditions were also found 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 9/11 exposure has been found to be associated with substance use, especially alcohol consumption [Vlahov et al, , ]. Higher levels of binge drinking have been observed among survivors 2 years [Boscarino et al, ] and 6 years [Welch et al, ] after 9/11. Physical proximity to the World Trade Center attacks predicted higher levels of alcohol consumption, even among those with no history of alcohol dependence [Hasin et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Addictive Behaviors 43 (2015) [89][90][91][92][93][94][95][96] Importantly, despite noteworthy evidence for a relationship between SE and subsequent SUD, several studies do not find an association between SE and SUD risk Keyes, Hatzenbuehler, Grant, & Hasin, 2012;North et al, 2005;Vlahov et al, 2006). This could be partially attributable to a methodological factor since several studies examined exposure to a stressful events in general instead of taking into account type and severity of concrete perceived stressors which can vary between individuals experiencing SE (Jones et al, 2013;Vogt et al, 2011aVogt et al, , 2011bWelch et al, 2014). Probably even more importantly, the heterogeneity in findings might indicate the relevance of moderating factors in the relation between SE and the risk for SUDs.…”
Section: Introductionmentioning
confidence: 89%